PENYIMPANGAN MAKSIM KESANTUNAN JURI DAN PEWARA DALAM KONTEKS D’ACADEMY ASIA TAHUN 2019 - Melenia Wati, Shinta; Ngatmini, Ngatmini; Utami, H.R. (Universitas Islam Sumatera Utara, 2023)
The purpose of this study is to describe the politeness deviations contained in the speeches of the judges and presenters in the D'academy Asia contest. Therefore this research is descriptive qualitative. The data of this study are in the form of the speeches of the judges and presenters in the D'Academy Asia contest which indicate deviations from the maxim of politeness. The data collection method uses recording techniques, note-taking techniques are followed by transcripts and classifying. The technique of presenting the results of data analysis using informal methods.The results of the study showed deviations from the politeness maxims carried out by the jury including: deviations from the maxims of tact, generosity, modesty, agreement and sympathy. Deviations from the politeness maxim by the speaker include the maxims of wisdom, generosity, appreciation and sympathy. The purpose of this study is to describe the politeness deviations contained in the speeches of the judges and presenters in the D'academy Asia contest. Therefore this research is descriptive qualitative. The data of this study are in the form of the speeches of the judges and presenters in the D'Academy Asia contest which indicate deviations from the maxim of politeness. The data collection method uses recording techniques, note-taking techniques are followed by transcripts and classifying. The technique of presenting the results of data analysis using informal methods.The results of the study showed deviations from the politeness maxims carried out by the jury including: deviations from the maxims of tact, generosity, modesty, agreement and sympathy. Deviations from the politeness maxim by the speaker include the maxims of wisdom, generosity, appreciation and sympathy.